Qiraatul Bayyati: A Method for Improving Quranic Recitation Competency in Tajweed Learning - Imam Rofi'i, Huda; Taruddin, Taruddin; Winda Meri, Susila; Dedi, Rianto; Qurrotush, Sholihah (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Students' difficulty in reading the Quran with correct recitation is one of the main obstacles in learning Tajweed. The Qiraatul Bayyati method can serve as a solution to this issue by making it easier for students to remember and understand the rhythm of recitation. This study aims to analyze how the Qiraatul Bayyati method can improve student learning outcomes in Tajweed. This research employed classroom action research with a participant-observation approach. Data were collected from the Tajweed teacher and 18 students using observation and testing techniques. After data collection, the results were analyzed through descriptive statistical analysis, presented in tables and histogram graphs, while observation data were grouped based on planning, implementation, evaluation, and reflection activities. The findings showed an increase in the average student score from 28% in the pre-cycle to 88.8% after the second cycle. This data demonstrates that the use of the Qiraatul Bayyati method in Tajweed classes creates a conducive learning environment, motivating students and preventing boredom in the learning process.